1996
DOI: 10.1177/009365096023003001
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events and Television Viewing

Abstract: Mood management theory predicts that people experiencing stress use television to block anxious thoughts and to replace dysphoric moods. In a survey of 491 adults, Study 1 found that stress as measured by life events was unrelated to time spent TV viewing but for women, was positively related to scores on a scale of television addiction. In Study 2, viewing diaries of 329 families were examined with relation to stressful life events. Mood management theory was confirmed in that stress was associated with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 17 publications
4
128
0
1
Order By: Relevance
“…This may be plausibly interpreted in light of mood management theory, as stressful life events are likely to be associated with strain and exhausted resources. In the Anderson et al (1996) study, stressed men tended to watch more violent action, and horror programming, while stressed women tended to watch more game shows. A panel study by Brosius, Rossmann, and Elnain (1999) likewise indicated that individuals who felt more depleted following an increased workload in their jobs spent more time watching entertaining television content.…”
Section: Recovery Of Physiological Resourcesmentioning
confidence: 95%
See 1 more Smart Citation
“…This may be plausibly interpreted in light of mood management theory, as stressful life events are likely to be associated with strain and exhausted resources. In the Anderson et al (1996) study, stressed men tended to watch more violent action, and horror programming, while stressed women tended to watch more game shows. A panel study by Brosius, Rossmann, and Elnain (1999) likewise indicated that individuals who felt more depleted following an increased workload in their jobs spent more time watching entertaining television content.…”
Section: Recovery Of Physiological Resourcesmentioning
confidence: 95%
“…Anderson, Collins, Schmitt, and Jacobvitz (1996) note, for example, that stressful life events predict length of exposure to televised entertainment, particularly comedy shows. This may be plausibly interpreted in light of mood management theory, as stressful life events are likely to be associated with strain and exhausted resources.…”
Section: Recovery Of Physiological Resourcesmentioning
confidence: 99%
“…In relation to media use, Zillman (1982;Zillman & Bryant, 1985) investigated the relationship between stress and television viewing and suggested that television can temporarily alleviate the negative feelings from stress by displacing anxious thoughts. This led researchers to propose that some viewers may use the television primarily to relieve stress which could lead to feelings that were addictive in nature (Anderson & Collin, 1996). Whang, Lee & Chang (2003) reported that work-related stress significantly increased internet use amongst people who displayed symptoms of internet addiction, while those who were not excessive internet users instead reported higher levels of drinking when stressed.…”
Section: Perceived Stressmentioning
confidence: 99%
“…A common hypothesis is that viewers use television to relieve stress (Anderson & Collin, 1996). Zillmann proposed that TV can temporarily alleviate the negative affects of stress by displacing anxious thoughts and by substituting negative affect with positive affect (Zillmann, 1982).…”
Section: Stress Reduction and Tablet Usementioning
confidence: 99%